TI_GERICHTE 11.2017.118 vom 11. Dezember 2018 , Esecuzione di decisioni: multa disciplinare per ogni giorno d'inadempimento - TI Tribunale d'appello (2018)
Esecuzione di decisioni: multa disciplinare per ogni giorno d'inadempimento